The Effect of Communication Quality and Information Quality at Education Fairs on Indonesian Digital Native Students’ Intention to Study Abroad - Umi Aslamiyah; Teofilus Teofilus; Trianggoro Wiradinata; Bima Yatna Anugerah Ramadhani (Al-Qalam Institue, 2026)
Education fairs are important service encounters in international higher education marketing because they connect prospective students with foreign universities through direct communication and information exchange. This study examines how communication quality and information quality at education fairs influence Indonesian digital natives' intention to study abroad, with student motivation as a mediating mechanism. A quantitative explanatory survey was conducted with 346 Indonesian respondents who had plans to study abroad and had attended an education fair within the previous 12 months. The data were analyzed using SPSS for respondent profiling and PLS-SEM with SmartPLS 4 for measurement and structural model evaluation. The findings show that communication quality positively affects student motivation (β = .256, p = .017), information quality positively affects student motivation (β = .422, p < .001), and student motivation strongly affects intention to study abroad (β = .800, p < .001). However, the direct effects of communication quality and information quality on intention are not significant. Motivation significantly mediates both relationships, indicating indirect-only mediation. The model explains 64.0% of the variance in intention to study abroad.